Nonaqueous electrolyte and lithium secondary battery containing same
A coumarin-based additive in the non-aqueous electrolyte addresses gas generation and electrode deterioration in high-voltage lithium secondary batteries by scavenging active oxygen and forming a stable SEI film, enhancing battery life and performance.
Patent Information
- Application Number
- JP2024542381
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-02-08
- Filing Date
- 2023-02-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-02-08
AI Technical Summary
High-voltage lithium secondary batteries face issues with gas generation and electrode deterioration due to electrolyte decomposition and active oxygen production during high-voltage activation, leading to reduced battery life and performance.
Incorporation of a coumarin-based compound with specific functional groups as an additive in the non-aqueous electrolyte to scavenge active oxygen and form a stable solid electrolyte interface (SEI) film, reducing gas generation and enhancing battery life under high voltage conditions.
The coumarin-based compound effectively suppresses gas production and electrode degradation, improving battery life and performance by reacting with active oxygen before it can decompose the organic solvent, forming a robust SEI film that stabilizes the electrode interface.
Smart Images

Figure 2025502386000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0016541, filed on February 8, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a non-aqueous electrolyte solution and a lithium secondary battery containing the same, and more particularly to a non-aqueous electrolyte solution containing a coumarin-based compound having at least one substituent, and a lithium secondary battery containing the same. [Background technology]
[0003] In recent years, interest in energy storage technology has been growing, and its application fields have expanded to include mobile phones, camcorders, and laptop computers, as well as the energy of electric vehicles. Accordingly, efforts in the research and development of electrochemical devices are being made concrete.
[0004] Among electrochemical devices, there has been growing interest in the development of chargeable and dischargeable secondary batteries. In particular, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of high operating voltage and extremely high energy density.
[0005] Lithium secondary batteries are generally manufactured by forming an electrode assembly by interposing a separator between a positive electrode including a positive electrode active material containing a lithium-containing transition metal oxide and a negative electrode including a negative electrode active material capable of storing lithium ions, inserting the electrode assembly into a battery case, injecting a non-aqueous electrolyte that serves as a medium for transferring lithium ions, and then sealing the battery case. The non-aqueous electrolyte typically includes a lithium salt and an organic solvent capable of dissolving the lithium salt.
[0006] In recent years, with the increasing demand for secondary batteries having high energy density, such as batteries for electric vehicles, high-voltage secondary batteries that are driven at high voltages have been actively developed. However, when the driving voltage increases, the decomposition of the electrolyte due to structural collapse, transition metal elution, gas generation, etc. is accelerated on the surface of the positive electrode, which causes a problem of a rapid decrease in the life characteristics of the battery.
[0007] In recent years, in order to reduce the manufacturing cost of batteries for electric vehicles, development has been carried out on batteries that use manganese-rich (Mn-rich) perlithiated positive electrode active materials, which are cheaper and more stable than conventional lithium-nickel-based positive electrode active materials. Batteries that use manganese-rich perlithiated positive electrode active materials are required to undergo an initial activation process at a high voltage of 4.6 V or more, but there is a problem that active oxygen is generated in the activation process, which causes side reactions with the electrolyte and increases resistance.
[0008] Therefore, there is a need for the development of a non-aqueous electrolyte that can suppress gas generation and positive electrode deterioration under high voltage conditions. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made to solve the above problems, and aims to provide a non-aqueous electrolyte that contains a coumarin compound having at least one functional group as an additive, thereby removing active oxygen generated under high voltage conditions, thereby suppressing the generation of gas and the production of low-temperature by-products.
[0010] Another object of the present invention is to provide a lithium secondary battery that contains the above-mentioned nonaqueous electrolyte and thus exhibits excellent life characteristics and swelling characteristics even under high voltage conditions. [Means for solving the problem]
[0011] According to one embodiment, the present invention provides a non-aqueous electrolyte comprising an organic solvent, a lithium salt, and a coumarin-based compound represented by the following Chemical Formula 1:
[0012] [ka]
[0013] In the above Chemical Formula 1, R is a substituent containing one or more elements selected from the group consisting of C, O, N, B, S, P, Si, and F, and n is an integer of 1 to 6. Specifically, R may contain a halogen, a nitrile group, an alkynyl group, a propargyl group, an ester group, an ether group, a ketone group, a carboxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a boron group, a borate group, an isocyanate group, an isothiocyanate group, a silyl group, a siloxane group, or a combination thereof. More specifically, R may be a nitrile group, an alkynyl group having 2 to 10 carbon atoms, a propargyl group, -COOR', -O-R'', -COR''', or an alkyl group having 1 to 10 carbon atoms which may or may not be substituted with at least one halogen, in which case R' may be a propargyl group, R'' may be a propargyl group or a silyl group substituted with at least one alkyl group having 1 to 5 carbon atoms, and R''' may be an alkyl group having 1 to 5 carbon atoms which may or may not be substituted with at least one halogen.
[0014] More specifically, the coumarin compound may be a compound represented by the following Chemical Formula 1-1 or 1-2.
[0015] [ka]
[0016] [ka]
[0017] In Chemical Formula 1-1 and Chemical Formula 1-2, R may be a substituent containing one or more elements selected from the group consisting of C, O, N, B, S, P, Si, and F, and specifically may contain a halogen, a nitrile group, an alkynyl group, a propargyl group, an ester group, an ether group, a ketone group, a carboxy group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a boron group, a borate group, an isocyanate group, an isothiocyanate group, a silyl group, a siloxane group, or a combination thereof. More specifically, R may be a nitrile group, an alkynyl group having 2 to 10 carbon atoms, a propargyl group, -COOR', -O-R'', -COR''', or an alkyl group having 1 to 10 carbon atoms which may or may not be substituted with at least one halogen, in which case R' may be a propargyl group, R'' may be a propargyl group or a silyl group substituted with at least one alkyl group having 1 to 5 carbon atoms, and R''' may be an alkyl group having 1 to 5 carbon atoms which may or may not be substituted with at least one halogen.
[0018] More specifically, the coumarin compound may be selected from the group consisting of compounds represented by the following Chemical Formulas 1A to 1G.
[0019] [ka]
[0020] [ka]
[0021] [ka]
[0022] [ka]
[0023] [ka]
[0024] [ka]
[0025] [ka]
[0026] Meanwhile, the coumarin compound may be contained in an amount of 0.5 to 3% by weight, preferably 0.5 to 2% by weight, and more preferably 0.5 to 1% by weight, based on the total weight of the non-aqueous electrolyte.
[0027] The non-aqueous electrolyte according to the present invention may further contain a halogenated cyclic carbonate, which may be preferably fluoroethylene carbonate. The halogenated cyclic carbonate may be contained in an amount of 0.5 to 10% by weight, preferably 0.5 to 8% by weight, more preferably 1 to 5% by weight, based on the total weight of the non-aqueous electrolyte.
[0028] According to another embodiment, the present invention provides a lithium secondary battery including a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and the non-aqueous electrolyte according to the present invention described above.
[0029] Preferably, the positive electrode active material may include a lithium manganese-based oxide represented by the following formula 2:
[0030] [Chemical formula 2] Li 1+a [Ni b Coc Mn d M 1 e O 2+a
[0031] In Chemical Formula 2, 0.05 ≦ a ≦ 1, 0 ≦ b ≦ 0.5, 0 ≦ c ≦ 0.1, 0.5 ≦ d ≦ 1.0, 0 ≦ e ≦ 0.2, and M 1 is at least one or more metal ions selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0032] More specifically, the positive electrode active material may contain a lithium manganese-based oxide represented by the following Chemical Formula 2-1.
[0033] [Chemical Formula 2-1] XLi2MnO3·(1-X)Li[Ni 1-y-z-w Mn y Co z M 1 w O2
[0034] In Chemical Formula 2-1, 0.3 ≦ X ≦ 0.5, 0.5 ≦ y < 1, 0 ≦ z ≦ 0.3, 0 ≦ w ≦ 0.2, and M 1 is at least one or more metal ions selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0035] On the other hand, the negative electrode active material may contain a silicon-based negative electrode active material. The silicon-based negative electrode active material is, for example, Si, SiO m (where 0 < m ≦ 2), Si-C composite, Si-M a alloy (M a is one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), and may be selected from the group consisting of combinations thereof. If necessary, the negative electrode active material may further contain a carbon-based negative electrode active material.
Advantages of the Invention
[0036] The coumarin compound of Chemical Formula 1 used as an additive for the non-aqueous electrolyte according to the present invention has a higher reaction energy with active oxygen than organic solvents such as ethylene carbonate, and therefore, when active oxygen is generated, it binds with the active oxygen before the organic solvent does. Therefore, when the non-aqueous electrolyte contains the coumarin compound of Chemical Formula 1, the active oxygen generated in the high voltage battery is scavenged by the coumarin compound, and decomposition of the organic solvent by the active oxygen can be suppressed, thereby minimizing the generation of gas and low-molecular by-products generated by decomposition of the organic solvent.
[0037] In addition, the coumarin compound of Chemical Formula 1 contains a substituent containing one or more elements selected from the group consisting of C, O, N, S, P, Si, and F, and forms an SEI film on the surface of the positive electrode and / or negative electrode, thereby suppressing direct contact between the electrode and the electrolyte, reducing gas generation and swelling at high temperatures, and improving the lifespan.
[0038] When the nonaqueous electrolyte according to the present invention is applied to a lithium secondary battery that uses a positive electrode active material containing a perlithiated manganese oxide and that requires a high-voltage activation step of 4.6 V or more, it is possible to obtain particularly excellent effects in terms of gas reduction and resistance reduction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] The present invention will be specifically described below.
[0040] Unless otherwise defined, the term "substituted" means that at least one or more hydrogens bonded to a carbon are replaced with an element other than hydrogen, for example, that at least one or more hydrogens bonded to a carbon are replaced with a halogen, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, a heterocycloalkyl group having 3 to 12 carbon atoms, a heterocycloalkenyl group having 3 to 12 carbon atoms, an aryloxy group having 6 to 12 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, a nitrile group, an aryl group having 6 to 20 carbon atoms, a heteroaryl group having 2 to 20 carbon atoms, a haloaryl group having 6 to 20 carbon atoms, or the like.
[0041] [Non-aqueous electrolyte] The non-aqueous electrolyte according to the present invention contains (1) an organic solvent, (2) a lithium salt, and (3) a coumarin-based compound represented by the following chemical formula 1.
[0042] (1) Organic Solvent In the present invention, the organic solvent may include a cyclic carbonate solvent, a linear carbonate solvent, a linear ester solvent, or a mixture thereof.
[0043] The cyclic carbonate solvent is a high-viscosity organic solvent that has a high dielectric constant and is therefore easy to dissociate the lithium salt in the electrolyte, and may be, for example, at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate. Specifically, the cyclic carbonate solvent may be ethylene carbonate, propylene carbonate, or a mixture thereof.
[0044] The linear carbonate-based solvent is an organic solvent having low viscosity and low dielectric constant, and may be, for example, at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate.
[0045] The linear ester solvent may be, for example, at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0046] Preferably, the organic solvent may be a mixture of a cyclic carbonate solvent and a linear carbonate solvent. In this case, the cyclic carbonate solvent and the linear carbonate solvent may be mixed in a volume ratio of 10-40:60-90, preferably 10-30:70-90, more preferably 15-30:70-85. When the content of the cyclic carbonate solvent and the linear carbonate solvent is within the above range, both high dielectric constant and low viscosity characteristics are satisfied, and excellent ion conductivity characteristics can be realized.
[0047] (2) Lithium salt As the lithium salt used in the present invention, various lithium salts that are commonly used in electrolytes for lithium secondary batteries can be used without any limitation. For example, the lithium salt has Li as a cation. + and as an anion, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , AlO4 - , AlCl4 - , PF6 - , SbF6 -, AsF6 - , B 10 Cl 10 - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , C4F9SO3 - , CF3CF2SO3 - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CH3SO3 - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - The present invention may include at least one selected from the group consisting of:
[0048] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiAlO4, LiAlCl4, LiPF6, LiSbF6, LiAsF6, LiB 10 Cl 10, LiBOB (LiB (C2O4)2), LiCF3SO3, LiTFSI (LiN (SO2CF3)2), LiFSI (LiN (SO2F)2), LiCH3SO3, LiCF3CO2, LiCH3CO2, and LiBETI (LiN (SO2CF2CF3)2). Specifically, the lithium salt may include a single substance selected from the group consisting of LiBF4, LiClO4, LiPF6, LiBOB (LiB (C2O4)2), LiCF3SO3, LiTFSI (LiN (SO2CF3)2), LiFSI (LiN (SO2F)2), and LiBETI (LiN (SO2CF2CF3)2), or a mixture of two or more substances.
[0049] The lithium salt may be contained in the electrolyte at a concentration of 0.8 M to 4 M, preferably 0.8 M to 2 M, and more preferably 0.8 M to 1.6 M. When the concentration of the lithium salt satisfies the above range, the lithium ion transportence number (Li+ transference number) and the degree of dissociation of lithium ions are improved, and the output characteristics of the battery can be improved.
[0050] (3) Coumarin compounds The non-aqueous electrolyte according to the present invention contains a coumarin-based compound represented by the following chemical formula 1.
[0051] [ka]
[0052] In the above Chemical Formula 1, R is a substituent containing one or more elements selected from the group consisting of C, O, N, B, S, P, Si, and F, and n is an integer of 1 to 6. Specifically, R may contain a halogen, a nitrile group, an alkynyl group, a propargyl group, an ester group, an ether group, a ketone group, a carboxy group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a boron group, a borate group, an isocyanate group, an isothiocyanate group, a silyl group, a siloxane group, or a combination thereof. More specifically, R may be a nitrile group, an alkynyl group having 2 to 10 carbon atoms, a propargyl group, -COOR', -O-R'', -COR''', or an alkyl group having 1 to 10 carbon atoms which may or may not be substituted with at least one halogen, in which case R' may be a propargyl group, R'' may be a propargyl group or a silyl group substituted with at least one alkyl group having 1 to 5 carbon atoms, and R''' may be an alkyl group having 1 to 5 carbon atoms which may or may not be substituted with at least one halogen.
[0053] The coumarin compound represented by Chemical Formula 1 has a higher reaction energy with active oxygen than organic solvents such as ethylene carbonate, and therefore binds to active oxygen before the organic solvent when active oxygen is generated. Therefore, when the coumarin compound represented by Chemical Formula 1 is included in the non-aqueous electrolyte, active oxygen generated in the initial activation stage of the high-voltage battery is scavenged by the coumarin compound, and decomposition of the organic solvent by active oxygen can be suppressed, thereby minimizing the generation of gas and low-molecular by-products generated by decomposition of the organic solvent.
[0054] In addition, the coumarin compound of Chemical Formula 1 contains a substituent containing one or more elements selected from the group consisting of C, O, N, B, S, P, Si, and F, and forms an SEI film on the surface of the positive electrode and / or negative electrode, thereby suppressing direct contact between the electrode and the electrolyte, reducing gas generation and swelling at high temperatures, and improving the lifespan.
[0055] More specifically, the coumarin compound may be a compound represented by the following Chemical Formula 1-1 or 1-2.
[0056] [ka]
[0057] [ka]
[0058] In Chemical Formula 1-1 and Chemical Formula 1-2, R may be a substituent containing one or more elements selected from the group consisting of C, O, N, B, S, P, Si, and F, and specifically may contain a halogen, a nitrile group, an alkynyl group, a propargyl group, an ester group, an ether group, a ketone group, a carboxy group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a boron group, a borate group, an isocyanate group, an isothiocyanate group, a silyl group, a siloxane group, or a combination thereof. More specifically, R may be a nitrile group, an alkynyl group having 2 to 10 carbon atoms, a propargyl group, -COOR', -O-R'', -COR''', or an alkyl group having 1 to 10 carbon atoms which may or may not be substituted with at least one halogen, in which case R' may be a propargyl group, R'' may be a propargyl group or a silyl group substituted with at least one alkyl group having 1 to 5 carbon atoms, and R''' may be an alkyl group having 1 to 5 carbon atoms which may or may not be substituted with at least one halogen.
[0059] More specifically, the coumarin compound may be selected from the group consisting of compounds represented by the following Chemical Formulas 1A to 1G.
[0060] [ka]
[0061] [ka]
[0062] [ka]
[0063] [ka]
[0064] [ka]
[0065] [ka]
[0066] [ka]
[0067] Meanwhile, the coumarin-based compound may be included in an amount of 0.5% by weight to 3% by weight, preferably 0.5% by weight to 2% by weight, more preferably 0.5% by weight to 1% by weight, based on the total weight of the non-aqueous electrolyte. When the content of the coumarin-based compound satisfies the above range, a strong SEI film can be formed on the positive electrode and the negative electrode, and oxygen radical compounds generated at the positive electrode can be effectively removed, thereby helping to improve the battery performance. If the content of the coumarin-based compound is too high, the resistance increases, which may adversely affect the battery performance.
[0068] (4) Other ingredients Meanwhile, the non-aqueous electrolyte according to the present invention may further contain, in addition to the above components, an additive in order to further improve the physical properties of the secondary battery, although this is not essential.
[0069] Examples of such additives include at least one selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sultone compounds, sulfate compounds, phosphate compounds, borate compounds, benzene compounds, amine compounds, silane compounds, and lithium salt compounds.
[0070] The cyclic carbonate compound may be, for example, vinylene carbonate (VC) or vinyl ethylene carbonate (VEC).
[0071] The halogen-substituted carbonate compound may be, for example, fluoroethylene carbonate (FEC).
[0072] The sultone compound may be, for example, 1,3-propane sultone, 1,3-propene sultone, and the like.
[0073] The sulfate compound may be, for example, ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).
[0074] The phosphate-based compound may be, for example, one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, trimethylsilylphosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.
[0075] The borate-based compound may be, for example, tetraphenylborate, lithium oxalyldifluoroborate (LiODFB), and the like.
[0076] The benzene-based compound may be, for example, fluorobenzene, the amine-based compound may be, for example, triethanolamine or ethylenediamine, and the silane-based compound may be, for example, tetravinylsilane.
[0077] The lithium salt compound is a compound different from the lithium salt contained in the nonaqueous electrolyte, and may be one or more compounds selected from the group consisting of LiPO2F2, LiODFB, LiBOB (lithium bis(oxalato)borate (LiB(C2O4)2), and LiBF4.
[0078] On the other hand, the additives may be used alone or in combination of two or more kinds.
[0079] The total amount of the additives may be 0.1 to 20% by weight, preferably 0.1 to 15% by weight, based on the total weight of the electrolyte solution. When the additives are contained within the above range, a stable coating is formed on the electrode, which can suppress the ignition phenomenon during overcharge, and can prevent side reactions from occurring during the initial activation process of the secondary battery, and can prevent the additives from remaining or being precipitated.
[0080] Among the additives, it is particularly preferred to further include a halogen-substituted carbonate-based compound, for example, fluoroethylene carbonate (FEC). When the halogen-substituted carbonate-based compound is used as an additive, the oxidation stability of the electrolyte is increased, and a high voltage improvement effect can be obtained, and an SEI film is formed on the surface of the positive electrode, and the interface of the positive electrode is stabilized, and the effect of improving the long life characteristics can be obtained. However, when fluoroethylene carbonate is used alone, there is a risk of side effects such as excessive oxidative decomposition reaction occurring at the interface of the positive electrode, LiF components being deposited on the surface of the positive electrode to increase resistance, CO2 gas generation and HF generation side reactions increasing, and accelerating the decomposition reaction of the electrolyte. However, when the halogen-substituted carbonate-based compound and the coumarin-based compound are used together, the positive electrode film formation mechanism of the coumarin-based compound suppresses the positive electrode oxidation reaction of the halogen-substituted carbonate-based compound, and the occurrence of the above-mentioned side effects can be minimized.
[0081] In this case, the halogen-substituted carbonate-based compound may be contained in an amount of 0.5% by weight to 10% by weight, preferably 0.5% by weight to 8% by weight, more preferably 1% by weight to 5% by weight, based on the total weight of the non-aqueous electrolyte. When the content of the halogen-substituted carbonate-based compound satisfies the above range, the oxidation stability of the electrolyte is increased, thereby improving high voltage performance, and the life characteristics are improved by forming an SEI film.
[0082] [Lithium secondary battery] Next, the lithium secondary battery according to the present invention will be described.
[0083] The lithium secondary battery according to the present invention includes a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a non-aqueous electrolyte. More specifically, it may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. At this time, the non-aqueous electrolyte is the non-aqueous electrolyte according to the present invention described above, that is, a non-aqueous electrolyte containing an organic solvent, a lithium salt, and a coumarin-based compound represented by Chemical Formula 1. Since the non-aqueous electrolyte has been described above, the description thereof is omitted, and other components will be described below.
[0084] 〔Positive Electrode〕 The positive electrode includes a positive electrode active material layer containing a positive electrode active material. Optionally, the positive electrode active material layer may further contain a conductive material and / or a binder.
[0085] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and various positive electrode active materials used in the art, such as lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (0 < Y < 1), LiMn 2-Z Ni Z O4 (0 < Z < 2), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (0 < Y1 < 1), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (0 < Z1 < 2), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p1 Co q1 Mn r1 )O2 (0 < p1 < 1, 0 < q1 < 1, 0 < r1 < 1, p1 + q1 + r1 = 1) or Li(Ni p2 Co q2 Mnr2 )O4 (0 < p2 < 2, 0 < q2 < 2, 0 < r2 < 2, p2 + q2 + r2 = 2), or a lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p3 Co q3 Mn r3 M s3 )O2 (M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p3, q3, r3, and s3 are the atomic fractions of the respective independent elements, where 0 < p3 < 1, 0 < q3 < 1, 0 < r3 < 1, 0 < s3 < 1, and p3 + q3 + r3 + s3 = 1) can be used, etc.
[0086] Preferably, the positive electrode active material may contain a hyperlithiated manganese-rich oxide in which Mn is contained in an amount of 50 mol% or more in all metals excluding lithium, and the molar ratio of lithium to transition metal exceeds 1.
[0087] When a lithium manganese oxide containing excess lithium is used as a positive electrode active material, the irreversible capacity of Si is compensated for by the excess lithium contained in the positive electrode active material in the initial activation process, so that the balance with the silicon-based negative electrode can be achieved without the need for a separate compensation material such as a sacrificial positive electrode material or a process of pre-compensating for lithium such as pre-lithiation. Specifically, the overlithiated manganese-rich oxide has a structure in which a layered (LMO2) and rock salt phase (Li2MnO3) are mixed in the positive electrode active material, and the irreversible capacity of Si is compensated for by the lithium generated during the decomposition of the lithium manganese oxide in the rock salt phase in the initial activation process. However, in order to achieve this, the initial activation process must be performed at a high voltage of 4.6 V or more, and active oxygen is generated during the process of decomposing the lithium manganese oxide in the rock salt phase. Active oxygen attacks and decomposes organic solvents such as ethylene carbonate, generating gas and antibody by-products that degrade the physical properties of the battery. However, in the present invention, since the non-aqueous electrolyte contains a coumarin-based compound that is more reactive with active oxygen than the organic solvent, the active oxygen generated in the initial activation process is bound to the coumarin-based compound before the organic solvent binds to the organic solvent, thereby minimizing side effects caused by the decomposition of the organic solvent.
[0088] Specifically, the lithium manganese oxide may be represented by the following chemical formula 2.
[0089] [Chemical formula 2] Li 1+a [Ni b Co c Mn d M 1 e ]O 2+a
[0090] In the above Chemical Formula 1, 0.05≦a≦1, 0≦b≦0.5, 0≦c≦0.3, 0.5≦d<1.0, 0≦e≦0.2 may be satisfied, preferably 0.05≦a≦1.0, 0.1≦b≦0.5, 0≦c≦0.1, 0.5≦d<1.0, 0≦e≦0.2 may be satisfied, and more preferably 0.10≦a≦0.50, 0.1≦b≦0.5, 0≦c≦0.1, 0.6≦d<1.0, 0≦e≦0.1 may be satisfied.
[0091] Also, M 1 may be at least one metal ion selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0092] More specifically, the lithium manganese oxide may be represented by the following chemical formula 2-1.
[0093] [Chemical formula 2-1] XLi2MnO3·(1-X)Li[Ni 1-y-z-w Mn y Co z M 1 w ]O2
[0094] In the above chemical formula 2-1, 0.1≦X≦0.5, 0.5≦y<1, 0≦z≦0.3, 0≦w≦0.2 may be satisfied, preferably 0.2≦X≦0.5, 0.5≦y<1, 0≦z≦0.1, 0≦w≦0.2, and more preferably 0.3≦X≦0.5, 0.6≦y<1, 0≦z≦0.1, 0≦w≦0.2.
[0095] Also, M 1 may be at least one metal ion selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
[0096] The lithium manganese oxide may be prepared by mixing a transition metal precursor and a lithium source material, followed by calcination. In this case, the transition metal precursor and the lithium source material may be mixed in amounts such that the molar ratio of total transition metals (Ni+Co+Mn) to Li is 1:1.05 to 1:2, the calcination temperature may be 600°C to 1000°C, the calcination time may be 5 hours to 30 hours, and the calcination atmosphere may be an air atmosphere or an oxygen atmosphere, for example, an atmosphere containing oxygen at 20 volume % to 100 volume %.
[0097] Examples of the lithium source material include lithium-containing carbonates (e.g., lithium carbonate, etc.), hydrates (e.g., lithium hydroxide hydrate (LiOH·H2O)), hydroxides (e.g., lithium hydroxide), nitrates (e.g., lithium nitrate (LiNO3)), chlorides (e.g., lithium chloride (LiCl)), etc., and one of these can be used alone or a mixture of two or more can be used.
[0098] Meanwhile, the transition metal precursor may be in the form of a hydroxide, an oxide, or a carbonate. When a precursor in the form of a carbonate is used, it is more preferable in that a positive electrode active material having a relatively high specific surface area can be produced.
[0099] The transition metal precursor may be prepared by a co-precipitation process. For example, the transition metal precursor may be prepared by dissolving each transition metal-containing raw material in a solvent to prepare a metal solution, and then mixing the metal solution, an ammonium cation complexing agent, and a basic compound, and then carrying out a co-precipitation reaction. If necessary, an oxidizing agent or oxygen gas may be further added during the co-precipitation reaction.
[0100] In this case, the transition metal-containing raw material may be acetate, carbonate, nitrate, sulfate, halide, sulfide, etc. of each transition metal. Specifically, the transition metal-containing raw material may be NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4·H2O, manganese acetate, manganese halide, cobalt oxide, cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt acetate, cobalt halide, etc.
[0101] The ammonium cation complexing agent may be at least one selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, and (NH4)2CO3.
[0102] The basic compound may be at least one selected from the group consisting of NaOH, Na2CO3, KOH, and Ca(OH)2. The form of the precursor may vary depending on the type of basic compound used. For example, when NaOH is used as the basic compound, a precursor in the form of a hydroxide is obtained, and when Na2CO3 is used as the basic compound, a precursor in the form of a carbonate is obtained. When a basic compound and an oxidizing agent are both used, a precursor in the form of an oxide is obtained.
[0103] On the other hand, the positive electrode active material according to the present invention may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the average particle size D50 of the secondary particles may be 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 4 μm to 8 μm.
[0104] The positive electrode active material has a BET specific surface area of 1 m 2 / g or more, 3m 2 / g~8m 2 / g, or 4m 2 / g~6m 2 / g.
[0105] In addition, the positive electrode active material according to the present invention preferably has an initial irreversible capacity of about 5% to 70%, 5% to 50%, or 10% to 30%. When the initial irreversible capacity of the positive electrode active material satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be compensated for without a separate compensation material such as a sacrificial positive electrode material or a process of pre-compensating for lithium such as prelithiation.
[0106] On the other hand, examples of the conductive material include spherical or flaky graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, and other carbon-based materials, metal powder or metal fiber, such as copper, nickel, aluminum, and silver, conductive whiskers, such as zinc oxide and potassium titanate, conductive metal oxides, such as titanium oxide, and conductive polymers, such as polyphenylene derivatives, and any one of these may be used alone or in combination of two or more. The conductive material may be included in an amount of 0.1% by weight to 20% by weight, 1% by weight to 20% by weight, or 1% by weight to 10% by weight based on the total weight of the positive electrode active material layer.
[0107] Examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one of these can be used alone or a mixture of two or more can be used. The binder may be contained in an amount of 1% by weight to 20% by weight, 2% by weight to 20% by weight, or 2% by weight to 10% by weight based on the total weight of the positive electrode active material layer.
[0108] The positive electrode of the present invention as described above may be manufactured by a method known in the art for manufacturing a positive electrode. For example, the positive electrode may be manufactured by a method of dissolving or dispersing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, which is then coated on a positive electrode current collector, followed by drying and rolling, or a method of casting the positive electrode slurry on a separate support, peeling off the support, and laminating the resulting film on a positive electrode current collector.
[0109] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector usually has a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive force to the positive electrode active material layer. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0110] The solvent may be any solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more. The amount of the solvent used is not particularly limited as long as it is adjusted to an appropriate viscosity of the positive electrode composite, taking into consideration the coating thickness of the positive electrode composite, production yield, workability, and the like.
[0111] [Negative electrode] The negative electrode according to the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, as necessary.
[0112] As the negative electrode active material, various negative electrode active materials used in the art, such as silicon-based negative electrode active materials, carbon-based negative electrode active materials, metal alloys, etc., may be used.
[0113] Preferably, the negative electrode active material contains a silicon-based negative electrode active material.
[0114] The silicon-based negative electrode active material is, for example, Si, SiO m (where 0 < m < 2), Si-C composite, Si-M a alloy (M a is selected from one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), and may be selected from the group consisting of combinations thereof.
[0115] Also, the silicon-based negative electrode active material may be doped with M b metal, and in this case, the M b metal may be a Group 1 alkali metal element and / or a Group 2 alkaline earth metal element, for example, Li, Mg, etc. Specifically, the silicon negative electrode active material is M b metal-doped Si, SiO m (where 0 < m < 2), Si-C composite, etc. The metal-doped silicon-based negative electrode active material has a reduced active material capacity due to the doping element, but has high efficiency, so a high energy density can be realized.
[0116] Also, the silicon-based negative electrode active material may further include a carbon coating layer on the surface of the particles. In this case, the carbon coating amount may be 20% by weight or less, preferably 0.1% by weight to 20% by weight, based on the total weight of the silicon-based negative electrode active material. The carbon coating layer can be formed by methods such as dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD).
[0117] Also, the particle size D of the silicon-based negative electrode active material50 is 3 μm to 8 μm, preferably 4 μm to 7 μm, and D min ~D max The thickness is 0.5 μm to 30 μm, preferably 0.5 μm to 20 μm, and more preferably 1 μm to 15 μm.
[0118] In addition, the negative electrode may further include a carbon-based negative electrode active material as a negative electrode active material, if necessary. The carbon-based negative electrode active material may be, but is not limited to, artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, soft carbon, hard carbon, etc.
[0119] Meanwhile, the silicon-based negative electrode active material may be included in an amount of 1 wt % to 100 wt %, 1 wt % to 50 wt %, 1 wt % to 30 wt %, 1 wt % to 15 wt %, 10 wt % to 70 wt %, or 10 wt % to 50 wt % based on the total weight of the negative electrode active material.
[0120] The carbon-based negative electrode active material may be included in an amount of 0 wt% to 99 wt%, 50 wt% to 99 wt%, 70 wt% to 99 wt%, 85 wt% to 99 wt%, 30 wt% to 90 wt%, or 50 wt% to 90 wt%, based on the total weight of the negative electrode active material.
[0121] According to one embodiment, the negative electrode active material may be a mixture of a silicon-based negative electrode active material and a carbon-based negative electrode active material, and in this case, the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material may be 1:99 to 50:50, preferably 3:97 to 30:70, by weight ratio. When the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material satisfies the above range, the capacity characteristics are improved and the volume expansion of the silicon-based negative electrode active material is suppressed, thereby ensuring excellent cycle performance.
[0122] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material is in the above range, excellent capacity characteristics and electrochemical characteristics can be obtained.
[0123] Examples of the conductive material include spherical or flaky graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotube, multi-walled carbon nanotube, and other carbon-based materials, metal powder or metal fiber, such as copper, nickel, aluminum, or silver, conductive whiskers, such as zinc oxide or potassium titanate, conductive metal oxides, such as titanium oxide, or conductive polymers, such as polyphenylene derivatives, and any one of these may be used alone or in combination of two or more. The conductive material may be included in an amount of 0.1% by weight to 30% by weight, 1% by weight to 20% by weight, or 1% by weight to 10% by weight based on the total weight of the negative electrode active material layer.
[0124] Preferably, the conductive material is a single-walled carbon nanotube. When the single-walled carbon nanotube is used as the conductive material, a conductive path is uniformly formed on the surface of the negative electrode active material, thereby improving cycle characteristics.
[0125] Examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one of these can be used alone or a mixture of two or more can be used. The binder may be contained in an amount of 1% by weight to 20% by weight, 2% by weight to 20% by weight, or 2% by weight to 10% by weight based on the total weight of the negative electrode active material layer.
[0126] The negative electrode may have a single-layered negative electrode active material layer or a multi-layered structure composed of two or more layers. When the negative electrode active material layer has a multi-layered structure composed of two or more layers, each layer may have a different type and / or content of the negative electrode active material, binder, and / or conductive material. For example, the negative electrode according to the present invention may be formed such that the lower layer has a higher content of the carbon-based negative electrode active material than the upper layer, and the upper layer has a higher content of the silicon-based negative electrode active material. In this case, compared to the case where the negative electrode active material layer is formed as a single layer, an effect of improving fast charging performance can be obtained.
[0127] The negative electrode active material layer may have a porosity of 20% to 70% or 20% to 50%.
[0128] The negative electrode may be manufactured by a method known in the art, for example, by coating a negative electrode slurry prepared by dissolving or dispersing a negative electrode active material and, optionally, a binder and a conductive material in a solvent on a negative electrode current collector, rolling and drying the slurry, or by casting the negative electrode slurry on a separate support, peeling off the support, and laminating the resulting film on the negative electrode current collector.
[0129] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector usually has a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0130] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one of these may be used alone or a mixture of two or more of them may be used. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity of the negative electrode slurry in consideration of the coating thickness of the negative electrode composite, production yield, workability, etc.
[0131] [Separator] In the lithium secondary battery of the present invention, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used in lithium secondary batteries can be used without any particular limitation, and in particular, a separator that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc., may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0132] The lithium secondary battery according to the present invention can be effectively used in portable devices such as mobile phones, notebook computers, and digital cameras, and in electric vehicles such as hybrid electric vehicles (HEVs).
[0133] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0134] The battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); and power storage systems.
[0135] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0136] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for small devices, but also suitably as a unit battery in a medium- to large-sized battery module containing a large number of battery cells.
[0137] The present invention will now be described in more detail with reference to specific examples.
[0138] Comparative Example 1 LiPF6 was dissolved to a concentration of 1.2M in a non-aqueous organic solvent prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate in a volume ratio of 20:60:20, and then 0.5 wt% vinylene carbonate (VC), 0.5 wt% propane sultone (PS), 1 wt% ethylene sulfate (ESa), 0.5 wt% LiBF4, 1 wt% lithium difluorophosphate (LiDFP), and 3 wt% fluorinated ethylene carbonate (FEC) were added to prepare a non-aqueous electrolyte.
[0139] Comparative Example 2 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5% by weight of an unsubstituted coumarin compound represented by chemical formula A was further added.
[0140] [ka]
[0141] Example 1 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1A was further added.
[0142] Example 2 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 1 wt % of the compound represented by Chemical Formula 1A was further added.
[0143] Example 3 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1B was further added.
[0144] Example 4 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1C was further added.
[0145] Example 5 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1D was further added.
[0146] Example 6 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1E was further added.
[0147] Example 7 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1F was further added.
[0148] Example 8 A non-aqueous electrolyte was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of the compound represented by Chemical Formula 1G was further added.
[0149] <Manufacturing lithium secondary batteries> (Production of positive electrodes) Lithium manganese oxide (Li) is used as the positive electrode active material particle. 1.3 (Ni 0.35 Mn 0.65 )O 2.33A positive electrode active material slurry (solid content 48 wt%) was prepared by adding carbon black as a conductive material and polyvinylidene fluoride (PVDF) as a binder in a weight ratio of 96:1:3 to N-methyl-2-pyrrolidone (NMP) as a solvent. The positive electrode active material slurry was applied to a positive electrode current collector (aluminum thin film), dried, and roll pressed to prepare a positive electrode.
[0150] (Production of negative electrodes) Negative electrode active material (artificial graphite: SiO m A negative electrode active material slurry (solid content: 70 wt%) was prepared by adding a 95:2:3 weight ratio of PVDF as a binder and carbon black as a conductive material to NMP as a solvent. The negative electrode active material slurry was applied to a negative electrode current collector (Cu thin film), dried, and roll pressed to prepare a negative electrode.
[0151] (Secondary battery manufacturing) The positive and negative electrodes prepared as described above were laminated together with a polyethylene porous film in a conventional manner to prepare an electrode assembly, which was then placed in a pouch-shaped secondary battery case and the non-aqueous electrolyte prepared in Examples 1 to 8 and Comparative Examples 1 and 2 was injected to prepare a lithium secondary battery.
[0152] Experimental Example 1 Each lithium secondary battery manufactured as described above was subjected to a pre-aging step of storing at room temperature for 2 days to allow the electrolyte to be sufficiently wetted. Then, the batteries were stored at 45° C. and 0.5 kgf / cm 2 After charging to SOC 3% at 0.2C under pressure of 5kgf / cm, the battery was charged to SOC 17% at 0.3C under the same temperature and pressure conditions, and then charged to SOC 20% at 5kgf / cm. 2 The battery was charged to SOC 30% at 0.3 C under a pressure of 1000 MPa, and then subjected to high-temperature aging at 60° C. for 15 hours to perform a film stabilization and gas discharge process.
[0153] Next, 45℃, 5kgf / cm2 The positive electrode was activated by charging the battery at 0.3 C to 4.6 V under a pressure of 1000 V, and then discharging the battery at 0.5 C to 2 V to complete the activation process.
[0154] Meanwhile, the cell volumes of the lithium secondary batteries before and after the activation process were measured at room temperature by a buoyancy method, and the cell volume increase rate during the activation process was calculated by the following formula (1).
[0155] Equation (1): Cell volume change rate (%) = {(volume after positive electrode activation process - initial cell volume) / initial cell volume} x 100
[0156] The measurement results are shown in Table 1 below.
[0157] [Table 1]
[0158] In the activation process, since charging is performed up to a high voltage of 4.6V, reactive oxygen compounds are generated at the positive electrode, and the reactive oxygen compounds react with the electrolyte to generate gases such as CO and CO2. The more reactive oxygen compounds there are, the more gas is generated, and the cell volume increases. Therefore, a small increase in cell volume means a small amount of reactive oxygen compounds. From Table 1, it can be seen that the lithium secondary batteries of Examples 1 to 8 using a coumarin-based compound having one or more substituents as an additive have a small increase in cell volume after the activation process compared to Comparative Examples 1 and 2, which indicates that the coumarin-based compound having one or more substituents effectively removes reactive oxygen.
[0159] On the other hand, in Comparative Example 2, in which an unsubstituted coumarin compound was used as an additive, the cell volume increase rate was lower than that of Comparative Example 1, but was higher than that of Examples 1 to 8. That is, it can be seen that the use of a coumarin compound substituted with one or more functional groups has a better effect of suppressing gas generation than the use of an unsubstituted coumarin compound. This is believed to be because a strong SEI film is formed on the surface of the electrode by the functional groups substituted on the coumarin, thereby suppressing side reactions at the electrode interface and further suppressing the generation of activated gas.
[0160] Experimental Example 2 Each of the lithium secondary batteries manufactured as described above was activated in the same manner as in Experimental Example 1, and then fully charged to SOC100% at 4.35 V under conditions of CC / CV and 0.33 C at 25° C. Then, the fully charged lithium secondary batteries were stored at 60° C. for 8 weeks, and the cell volume increase rate and capacity retention rate were measured.
[0161] At this time, the capacity retention rate was calculated by substituting the discharge capacity of the lithium secondary battery measured before the high-temperature storage and the discharge capacity of the lithium secondary battery measured after the high-temperature storage into the following formula (2).
[0162] Equation (2): Capacity retention rate (%) = (discharge capacity after high-temperature storage / discharge capacity before high-temperature storage) × 100
[0163] The cell volume change rate was calculated by substituting the initial volume before high-temperature storage and the volume after high-temperature storage into the following formula (3).
[0164] Equation (3): Cell volume change rate (%) = {(volume after high-temperature storage - initial volume) / initial volume} x 100
[0165] The measurement results are shown in Table 2 below.
[0166] [Table 2]
[0167] It can be seen from Table 2 that the lithium secondary batteries of Examples 1 to 8, which used a coumarin-based compound containing one or more substituents as an additive, had a higher capacity retention rate and a smaller cell volume increase rate after high-temperature storage compared to the lithium secondary batteries of Comparative Examples 1 and 2. This is believed to be because a strong SEI film was formed on the surface of the electrode by the functional groups substituted by the coumarin, thereby suppressing side reactions at the electrode interface.
Claims
1. A non-aqueous electrolyte comprising an organic solvent, a lithium salt, and a coumarin-based compound represented by the following chemical formula 1: 【Chemistry 1】 (In the above Chemical Formula 1, R is a nitrile group, an alkynyl group having 2 to 10 carbon atoms, a propargyl group, -COOR', -O-R'', -COR''', or an alkyl group having 1 to 10 carbon atoms which may or may not be substituted with at least one halogen; R' is a propargyl group, R'' is a propargyl group or a silyl group substituted with at least one alkyl group having 1 to 5 carbon atoms, R''' is an alkyl group having 1 to 5 carbon atoms which is either substituted with at least one halogen or is unsubstituted, and n is an integer of 1 to 6.
2. The non-aqueous electrolyte according to claim 1, wherein the coumarin-based compound is a compound represented by the following chemical formula 1-1 or 1-2. 【Chemistry 2】 【Chemistry 3】 (In the above Chemical Formula 1-1 and Chemical Formula 1-2, R is a nitrile group, an alkynyl group having 2 to 10 carbon atoms, a propargyl group, -COOR', -O-R'', -COR''', or an alkyl group having 1 to 10 carbon atoms which may or may not be substituted with at least one halogen; R' is a propargyl group, R'' is a propargyl group or a silyl group substituted with at least one alkyl group having 1 to 5 carbon atoms, and R''' is an alkyl group having 1 to 5 carbon atoms which is either substituted with at least one halogen or is unsubstituted.
3. The non-aqueous electrolyte according to claim 1, wherein the coumarin-based compound is selected from the group consisting of compounds represented by the following Chemical Formulas 1A to 1G. 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】 【Chemistry 8】 【Chemistry 9】 【Chemistry 10】
4. 2. The non-aqueous electrolyte according to claim 1, wherein the coumarin compound is contained in an amount of 0.5% by weight to 3% by weight based on the total weight of the non-aqueous electrolyte.
5. The non-aqueous electrolyte of claim 1 further comprising a halogen-substituted cyclic carbonate.
6. The non-aqueous electrolyte according to claim 5 , wherein the halogen-substituted cyclic carbonate is fluoroethylene carbonate.
7. 7. The non-aqueous electrolyte according to claim 6, wherein the halogen-substituted cyclic carbonate is contained in an amount of 0.5% by weight to 10% by weight based on the total weight of the non-aqueous electrolyte.
8. a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; A lithium secondary battery comprising the nonaqueous electrolyte according to claim 1 .
9. The lithium secondary battery according to claim 8, wherein the positive electrode active material contains a perlithiated manganese-rich oxide containing 50 mol % or more of Mn in all metals excluding lithium and having a molar ratio of lithium to transition metals exceeding 1.
10. 10. The lithium secondary battery of claim 9, wherein the perlithiated manganese-rich oxide is represented by the following Chemical Formula 2: [Chemical formula 2] Li 1+a [Ni b Co c Mn d M 1 e ]O 2+a (In the above chemical formula 2, 0.05≦a≦1, 0≦b≦0.5, 0≦c≦0.3, 0.5≦d<1.0, 0≦e≦0.2, and M 1 is at least one metal ion selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
11. The lithium secondary battery according to claim 9, wherein the perlithiated manganese-rich oxide is represented by the following chemical formula 2-1: [Chemical formula 2-1] XLi 2 MnO 3 ・(1-^)L[Ni 1-y-z-w Mn y Co z M 1 w ]O 2 (In the above chemical formula 2-1, 0.1≦x≦0.5, 0.5≦y<1, 0≦z≦0.3, and 0≦w≦0.2; M 1 is at least one metal ion selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
12. The lithium secondary battery according to claim 8 , wherein the negative electrode active material comprises a silicon-based negative electrode active material.
13. The silicon-based negative electrode active material is Si, SiO m (where 0<m≦2), Si-C composite, Si-M a Alloy (M a is one or more selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), and combinations thereof.
14. The lithium secondary battery according to claim 12 , wherein the negative electrode active material further comprises a carbon-based negative electrode active material.
15. 9. The lithium secondary battery of claim 8, wherein the coumarin compound is selected from the group consisting of compounds represented by the following Formulas 1A to 1G: 【Chemistry 11】 【Chemistry 12】 【Chemistry 13】 【Chemistry 14】 【Chemistry 15】 【Chemistry 16】 【Chemistry 17】
Citation Information
Patent Citations
Non-aqueous electrolyte for lithium ion battery, and lithium ion battery
CN102569889A
Electrolyte for cell and non-aqueous electrolyte secondary cell
JP2001143748A
Two-phase cathode material for lithium batteries and its synthesis method
JP2014506387A
Lithium-rich manganese cathode material and manufacturing method thereof, and lithium ion battery
JP2018503218A
Nonaqueous electrolyte containing additive for nonaqueous electrolyte and lithium secondary battery containing the same
JP2024521798A